Perlindungan Hukum Hak Paten dan Keadilan Akses Obat Pasca Undang-Undang Nomor 65 Tahun 2024 - Johannes; Farah Amandasari; Naila Putri Azzahra; Vella Monica; Dessy Puspita Tjahjadi; Martaida Sinaga; Novianlee Nata; Karolus Nahas (Laskar Karya, 2025)
This study aims to analyze the legal protection of patent rights following the enactment of Law Number 65 of 2024 on Patents, as well as to examine its legal implications for equitable access to medicines in Indonesia. The background of this research stems from the need for a patent regulation framework that not only safeguards exclusive rights for patent holders but also ensures affordability and availability of essential medicines for the public. The focus is on two newly regulated mechanisms: parallel import and the Bolar provision, which are part of the TRIPS flexibilities adapted into national law. The research adopts a normative juridical method, employing statutory and conceptual approaches. The data were analyzed descriptively through literature review, regulatory comparisons, and interpretation of relevant international legal instruments, including the TRIPS Agreement and the Doha Declaration. The results indicate that Law No. 65/2024 introduces a more balanced paradigm of patent protection. Parallel import provides a legal basis for importing patented medicines from abroad without the domestic patent holder’s consent, as long as they are lawfully marketed in the country of origin. The Bolar provision allows generic manufacturers to conduct research and testing prior to patent expiry, enabling timely availability of generic medicines post-patent. The discussion concludes that although both mechanisms are normatively regulated, their effectiveness depends heavily on technical regulations, inter-agency coordination, and consistent policy evaluation. Overall, the law represents a strategic move toward a patent system that is inclusive and oriented toward public health equity.